An approach to the analysis of heat and mass transfer characteristics in indirect evaporative cooling with counter flow configurations. (May 2017) - Wan, Yangda; Ren, Chengqin; Xing, Li
Highlights: An approach is proposed to calculate average Nusselt and Sherwood numbers in IEC. A 2-D CFD model is used to simulate the IEC under various boundary conditions. Similarity analysis is performed to obtain the set of grouped dimensionless factors. The effects of the dimensionless parameters are studied in detail. Abstract: Indirect evaporative cooler (IEC), regarded as a zero pollution, inexpensive and energy efficient cooling device, has been used in many occasions. This paper aims at developing a new approach for analyzing the coupled heat and mass transfer characteristics in indirect evaporative cooling with counter flow configurations. Firstly, a two-dimensional computational fluid dynamics (2-D CFD) model is used to simulate the coupled heat and mass transfer processes. Then, a one-dimensional (1-D) model is used to analyze the fluid stream side average Nusselt number and the cooling air side average Nusselt and Sherwood numbers based on the numerical results of the 2-D model. Thus, the 1-D model can be used to retrieve the 2-D model results using those average Nusselt and Sherwood numbers obtained. This improved accuracy will help to promote the control technologies based on an electronic control unit (ECU) for the processes in similar indirect evaporative cooling devices involved. Further, a similarity analysis is presented to deduce the 2-D model equations into dimensionless forms with the purpose of obtaining the minimum set of grouped dimensionless factors affecting the average Nusselt and Sherwood numbers. Finally, the effects of the ratio of liquid water film to cooling air mass flow rate, cooling air inlet Reynolds number, cooling air inlet dimensionless temperature, fluid stream inlet Reynolds number, liquid water film inlet dimensionless temperature, the ratio of channel length to half width of cooling air channel and the ratio of fluid to cooling air channel width on the average Nusselt and Sherwood numbers are examined in detail.